Building Circular Products in an Emerging Economy: An Initial Exploration Regarding Practices, Drivers and Barriers : Case studies of new product development from medium and large Brazilian companies. Issue 1 (1st January 2020) - Jugend, Daniel; Camargo Fiorini, Paula de; Pinheiro, Marco Antonio Paula; da Silva, Hermes Moretti Ribeiro; Pais Seles, Bruno Michel Roman
The circular economy (CE) is an important approach and current trend in environmental sustainability. The implementation of the CE depends on the adoption of sustainable practices from the planning stages of new product development (NPD). Although the literature recognises the need to apply CE practices into NPD, few studies have tried to provide support for the issues based on real case studies. This article aims to identify and analyse practices, barriers and drivers to the development of circular products. To achieve this objective, a multiple case study was carried out in three medium and large Brazilian companies that have environmental concerns and, at the same time, are continuously involved in NPD activities. The results show that the companies' circular product designs already foresee waste and recycled components as raw materials. In addition, it was found that infrastructural aspects and low awareness of customers regarding sustainability are challenges to overcome. Finally, for the adoption of CE practices, regulatory legislation stood out as a significant driver. This article contributes to theory and practice by providing empirical evidence of how companies have planned to build circular products by incorporating circular practices into the NPD process.